Mammalgia in oncomammology practice - Головко, Т. С. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
In recent decades it have seen a growth of benign breast disease, in particular fibrocystic breasts. Pain in breasts at mastopathia is the most important cause of women visits to the doctor. There are cyclic breast pain (2/3 cases) and non-cyclic (1/3 of cases). Cyclic breast pain (mastalgia) is the most common type of pain that is associated with the menstrual cycle. Noncyclic breast pain does not relate with the usual menstrual cycle. Breast status is evaluated using X-ray and ultrasound mammography. If deviations during a physical examination were found, diagnostics may also include a puncture and study of hormone levels. At examination the physician should rule out cancer and infection. Administration of progesterone topically as a gel helps compensate it deficit directly in the tissues of breast and leads to degradation of small cysts in case of fibrocystic breast disease.